Analisis Kualitas Air Lindi dan Permukaan pada areal TPA Sowi Gunung dan Sekitarnya di Kabupaten Manokwari Papua Barat - Novaldi Laudi Angrianto; Jacob Manusawai; Anton S. Sinery (Program Pascasarjana Universitas Papua, 2021)
The aim of the research was to determine the quality of leachate water in the processing unit (IPAL) of TPA Sowi Gunung and the quality of surface water around the TPA in relation to the operation of the IPAL TPA.The method used in this research is descriptive method with cross sectional survey technique by collecting leachate samples from the IPAL unit and surface water samples from two springs around the landfill area accompanied by in situ measurements of pH parameters and continued with 6 parameter quality analysis others (TSS, TDS, BOD, COD, N-total, TOC) at the Laboratory of the Center for Environmental Research, University of Papua. The result of the research it is known that the parameters of pH, TSS, BOD, COD, N-total, and TOC in the TPA IPAL unit are categorized as under quality standards (PerMenLHK No.59 of 2016 concerning leachate quality standards for businesses and / or activities for final processing sites trash).In particular, the TDS parameter does not have a tolerance limit corresponding to this quality standard so that it becomes a separate consideration in its management considering that water with a high amount of dissolved solids> 1000 mg / L has an unpleasant taste, so it is not suitable for consumption.Likewise, the quality of surface water at 2 (two) observation points of springs through parameters of pH, TSS, TDS, BOD, COD, N-total, and TOC are categorized as under class I water quality standards according to PP No. 82 of 2001 concerning water quality management and water pollution control.